Establishment and Evaluation of the Novel Tetramethylammonium‐L‐Hydroxyproline Chiral Ionic Liquid Synergistic System Based on Clindamycin Phosphate for Enantioseparation by Capillary Electrophoresis. Issue 9 (11th June 2015) - Xu, Guangfu; Du, Yingxiang; Du, Fan; Chen, Jiaquan; Yu, Tao; Zhang, Qi; Zhang, Jinjing; Du, Shuaijing; Feng, Zijie
Abstract Much attention has been paid to chiral ionic liquids (ILs) in analytical chemistry, especially its application in capillary electrophoresis (CE) enantioseparation. However, the investigation of chiral ionic liquids synergistic systems based on antibiotic chiral selectors has been reported in only one article. In this work, a novel chiral ionic liquid, tetramethylammonium‐L‐hydroxyproline (TMA‐L‐Hyp), was applied for the first time in CE chiral separation to evaluate its potential synergistic effect with clindamycin phosphate (CP) as the chiral selector. As observed, significantly improved separation was obtained in this TMA‐L‐Hyp/CP synergistic system compared to TMA‐L‐Hyp or a CP single system. Several primary factors that might influence the separation were investigated, including CP concentration, TMA‐L‐Hyp concentration, buffer pH, types and concentrations of organic modifier, applied voltage, and capillary temperature. The best results were obtained with a 40 mM borax buffer (pH 7.6) containing 30 mM TMA‐L‐Hyp, 80 mM CP, and 20% (v/v) methanol, while the applied voltage and temperature were set at 20 kV and 20°C, respectively. Chirality 27:598–604, 2015. © 2015 Wiley Periodicals, Inc.